1986
DOI: 10.1200/jco.1986.4.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Tumor burden assessment and its implication for a prognostic model in advanced diffuse large-cell lymphoma.

Abstract: Previously untreated adult patients who presented with advanced diffuse large-cell lymphoma (DLCL) at diagnosis were studied to identify possible prognostic factors. One hundred five patients were seen between 1974 and 1981; 45 patients were stage III and 60 patients were stage IV. All patients received cyclophosphamide, doxorubicin, vincristine, prednisone, and bleomycin (CHOP-Bleo). Stage III patients also received radiation therapy alternated with chemotherapy. Overall survival was 50% at 5 years and 43% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(50 citation statements)
references
References 18 publications
1
46
0
3
Order By: Relevance
“…The prognostic value of the Ann Arbor distinction between stage III and IV disease remains uncertain. Several studies have reported similar survival figures for stage III and stage IV patients (Koziner et al, 1982;Jagganath et al, 1985;Todd et al, 1986;Laurence et al, 1982;Sweet et al, 1980), but Nathwani et al (1982) (Bierman et al, 1957;Ferraris et al, 1979;Jagannath et al, 1986;Schneider et al, 1980;Hagberg & Siegbahm, 1983). In this study, although serum LDH was shown to be an independent (Christensson et al, 1986;Morgan et al, 1986;Juneja et al, 1986), but few have investigated the prognostic significance of DNA content within the category of high grade lymphoma.…”
Section: Overall Survivalmentioning
confidence: 86%
“…The prognostic value of the Ann Arbor distinction between stage III and IV disease remains uncertain. Several studies have reported similar survival figures for stage III and stage IV patients (Koziner et al, 1982;Jagganath et al, 1985;Todd et al, 1986;Laurence et al, 1982;Sweet et al, 1980), but Nathwani et al (1982) (Bierman et al, 1957;Ferraris et al, 1979;Jagannath et al, 1986;Schneider et al, 1980;Hagberg & Siegbahm, 1983). In this study, although serum LDH was shown to be an independent (Christensson et al, 1986;Morgan et al, 1986;Juneja et al, 1986), but few have investigated the prognostic significance of DNA content within the category of high grade lymphoma.…”
Section: Overall Survivalmentioning
confidence: 86%
“…In these patients, the presence of bulky lesions is associated with an elevated local relapse rate and a poor prognosis [3, 4, 5, 6, 7]due to the persistence of microscopical residual disease even when a clinical complete remission is achieved after chemotherapy. To avoid this, consolidation radiotherapy to bulky lesions has been proposed [8, 9], but the worldwide experience is very limited, no retrospective series have been reported and a single randomized trial has been published [10].…”
Section: Introductionmentioning
confidence: 99%
“…Of all the biochemical indicators investigated in the lymphomas, serum lactic dehydrogenase (LDH) has enjoyed the most universal acceptance. Since the early report of Bierman et al (1957) many investigators have confirmed the value of serum LDH as a prognostic tool, notably Ferraris et al, 1979;Schneider et al, 1980;Fisher et al, 1981;Jagannath et al, 1986 andSwan et al, 1989. In their study of patients with advanced (stage III/IV) diffuse large cell NHL, Jagannath et al (1986) identified serum LDH and tumour burden as independent risk factors for survival and devised a model in which three distinct groups of patients could be identified based on the serum LDH being normal or elevated and tumour burden being low or heavy; the five year follow-up data revealed survival as 87%, 48% and 20% for the high, intermediate and low risk groups, respectively.…”
Section: Biochemical Markersmentioning
confidence: 97%
“…There is clearly a need to move towards systems which take more account of tumour bulk. Categorisations of patients as having low, intermediate or high tumour burden have been put forward as alternatives to the Ann Arbor system, notably a system based on the number of extensively involved nodal areas and the number of extranodal sites (Jagannath et al, 1986). Reappraisal of staging, as has been done for HD, and probably a more radical shift to an international system which grades tumour burden is now needed.…”
Section: Stagingmentioning
confidence: 99%